Pengaruh Disiplin, Gaya Kepemimpinan, Dan Motivasi Terhadap Produktivitas Karyawan (Studi Pada Pesenkopi Malang) - Alvin Ramadhon; Budi Wahono; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Food and beverage (FnB) is a business that is mushrooming in the city of Malang, especially in the beverage sector or Baverage, the competition is tight, thus pressing a company to work harder in order to maximize work productivity with the aim of providing the best service, Human Resources (HR) is an important asset for support the success of an organization. Human Resources are the implementers of all organizational policies so that they need to be equipped with adequate knowledge. In general, employee productivity is the ability of each person or company to produce something desired by utilizing resources effectively and efficiently. This research uses quantitative methods. Quantitative method with multiple regression analysis is a research method based on the philosophy of positivism used in population and sample research. This quantitative study uses several variables as important indicators according to their usefulness, namely the influence of discipline, leadership style, and motivation. The results of the study on Pesenkopi Malang with 70 respondents showed that discipline, leadership, and work motivation simultaneously had a very strong influence on productivity and the three indicators showed significant positive results. Keywords : Business, Human Resource, Effectivity, Diciplinary, Motivation,And Leadership Style